La raíz común de los enfoques “epistemológico” y “gnoseológico” de la pregunta por la ciencia del materialismo gnoseológico: el dualismo cartesiano - Fuentes, Juan B.; García Pérez, Natalia S. (Logos. Anales del Seminario de Metafísica, 2007)
This work tries to demonstrate, in first place, that the “gnoseological” approach to the question for the science defended by Gustavo Bueno in fact only fits in the gnoseological materialism, the theory proposed by Bueno, while adequationism, theoreticism and descriptionsm would be theories of the science that genuinely would adopt the “epistemological” approach. In second place, we sustain that the epistemological and gnoseological approaches are generated in the soul/body alternative outlined by Cartesian dualism, because while the first one conceives the subject that makes the sciences as a mere mind that operates with propositions or concepts “about the things”, the second one understands it as a (soulless) mechanical body that builds the sciences operating “with the things themselves”. Since in Descartes the soul is the instance that knows, the option for the body of the gnoseological materialism explains its (self) positioning regardless of the question of knowledge. Lastly, we examine some problems that this Cartesian notion of subject implicates for the gnoseological materialism’s conception of “human and ethological sciences”.